Affect, emotion, and subjectivity in early modern Muslim Empires new studies in Ottoman, Safavid, and Mughal art and culture - Rizvi, Kishwar (Arts and archaeology of the Islamic world, 2018)
Affect, Emotion and Subjectivity in Early Modern Muslim Empires presents new approaches to Ottoman Safavid and Mughal art and culture. Taking artistic agency as a starting point, the authors consider the rise in status of architects, the self-fashioning of artists, the development of public spaces, as well as new literary genres that focus on the individual subject and his or her place in the world. They consider the issue of affect as performative and responsive to certain emotions and actions, thus allowing insights into the motivations behind the making and, in some cases, the destruction of works of art. The interconnected histories of Iran, Turkey and India thus highlight the urban and intellectual changes that defined the early modern period